Reestruturação produtiva, educação, trabalho e trabalhadores nas empresas mineradoras de Catalão/GO - (:unkn) unknown (Universidade Federal de Goiás, 2018)
This dissertation studies in the empiress of History, Professional Master's in History: History, Culture and Training of Teachers by the Federal University of Goiás Regional Catalão (UFG-RC), in the line of research: History, society and educational practices. Based on interviews with Catalan mining companies, the company began its activities of 80 and 90, through the process of transformation in the form of work in Mineração in Catalão. We start from the thesis that as transformations that occurred were forged as strategies of intervention in the everyday of workers. The issues of job security, scanning, outsourcing and leadership in attempting to control the worker. With the development of the research and after a review of the premium banking, which were carried out these actions were reflections of the Productive Restructuring of Capital in the 20th Century. The stratégicas in situ were forced to intervene in the daily life of the workers, but were forced in an attempt to control the subofetividade of the workers during the working hours, but were able to control the subjectivity of the worker in a complete way. But the trial of the company was frustrated in part.
Keywords: Trabalhadores; Mineração; Reestruturação produtiva; CIENCIAS HUMANAS::HISTORIA